2020
DOI: 10.3390/healthcare8040397
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perception on the Effectiveness of Emergency Competence Learning through Simulation

Abstract: (1) Background: Simulation is a part of the day-to-day of the learning method in health sciences. The objective is to determine if the clinical simulation is useful for learning in the emergency setting, from the point of view of the nursing students. (2) Methods: A pre- and post-test exploratory study with an analytical and quasi-experimental design was used. The population is made up of nursing students from the Seville Red Cross Nursing Centre, who conducted a simulation exercise in the form of a drill for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For example, a study with a quasi-experimental design in the field of mental health showed that simulations improve students’ attitudes and enhanced their confidence and self-efficacy [ 22 ]. Other quasi-experimental design studies in the field of emergency medicine found significant and favourable relationships in the dimensions of satisfaction, confidence, and motivation following the performance of high-fidelity simulations by students [ 23 , 24 ]. Therefore, the benefits of high-fidelity simulations in terms of student learning calls for further research in this field [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study with a quasi-experimental design in the field of mental health showed that simulations improve students’ attitudes and enhanced their confidence and self-efficacy [ 22 ]. Other quasi-experimental design studies in the field of emergency medicine found significant and favourable relationships in the dimensions of satisfaction, confidence, and motivation following the performance of high-fidelity simulations by students [ 23 , 24 ]. Therefore, the benefits of high-fidelity simulations in terms of student learning calls for further research in this field [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 13 articles included (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in this study were published from 2015 to 2022, all in English. Regarding their origin, with seven (54%) were from Europe, four (31.0%) from Asia, and two (15.0%) from North America.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…Regarding the populations under study, eight articles (16,(18)(19)(20)(21)(22)(23)28) (61.5%) were carried out with nursing students and five articles (17,(24)(25)(26)(27) (38.5%) with medical students. For methodological design, 11 studies (16)(17)(18)(20)(21)(22)(23)(24)(26)(27)(28) (84.6%) are quantitative, 1 (7.7%) is qualitative, and another 1 (7.7%) is a systematic review.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…The survey questions were expected to be answered through a gradation scale ranging between complete agreement and complete disagreement in a 5-point Likert type scale focusing on "satisfaction", "confidence", "motivation", "clinical experience", and "decision making and technical abilities". The questionnaire was not originally designed to explore the efficacy of simulation-based training on pharmacy students but was taken from a preceding quality and satisfaction study exploring the impacts of simulationbased learning on nursing students (Guerrero-Martínez et al, 2020). The questionnaire was given to the participants for answering twice during the study, once during a meeting a week before the intervention and another time when the practice has been finished.…”
Section: Data Collectionmentioning
confidence: 99%